INOVASI ADMINISTRASI PUBLIK - Yosar Kardiat (Jurnal Pallangga Praja (JPP), 2022)
The ability to innovate, especially policy innovation supported by bureaucratic creativity, is very important.Innovation in Indonesia has developed rapidly but is still carried out relatively partially. It is said to bepartial because an innovation is not automatically connected to other innovations. In the perspective of thepublic sector, innovation creates new policies in overcoming public policy problems. an innovation in publicadministration is an effective, creative and unique answer to a new problem against an old one. Innovationis applied by local governments in order to improve public services. Through this breakthrough, it is hopedthat it can support the creation of services that are faster, easier, smarter, more comfortable, better andcheaper. This step is at the same time to accelerate the achievement of Indonesia’s vision and mission goals,as well as to strengthen the synergy between the central government and local governments.